Analysis of the Fungal Diversity and Community Structure in Sichuan Dark Tea During Pile-Fermentation - Yan, Kuan; Abbas, Manzar; Meng, Lina; Cai, Hongbing; Peng, Zhang; Li, Quanzi; El-Sappah, Ahmed H.; Yan, Linfeng; Zhao, Xianming (Frontiers in Microbiology, 2021)
The fungi present during pile-fermentation of Sichuan dark tea play a pivotal role in the development of its aroma and physical characteristics. Samples of tea leaves were collected on days 0 (YC-raw material), 8 (W1-first turn), 16 (W2-second turn), 24 (W3-third turn), and 32 (W4-out of pile) during pile-fermentation. High-throughput sequencing revealed seven phyla, 22 classes, 41 orders, 85 families, 128 genera, and 184 species of fungi. During fermentation, the fungal diversity index declined from the W1 to W3 stages and then increased exponentially at the W4 stage. A bar plot and heatmap revealed that Aspergillus, Thermomyces, Candida, Debaryomyces, Rasamsonia, Rhizomucor, and Thermoascus were abundant during piling, of which Aspergillus was the most abundant. Cluster analysis revealed that the W4 stage of fermentation is critical for fungal growth, diversity, and the community structure in Sichuan dark tea. This study revealed the role of fungi during pile-fermentation in the development of the essence and physical characteristics of Sichuan dark tea. This study comes under one of the Sustainable Development Goals of United Nations Organization (UNO) to “Establish Good Health and Well-Being.”